(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
This paper presentsan overview oftheprojectcost management, with particular emphasis onprojects co-financedfrom the EU.Author of the paper pointed out the differences in terminology of project management, he also presented the processes connected with cost management of projects, as well as the ways of classifying the project costs for decision-making. Furthermore, he explained the role of budgeting in planning and controlling the costs of the European project.